Vaccination coverage and preventable diseases in Peru: Reflections on the first diphtheria case in two decades during the midst of COVID-19 pandemic - Mezones-Holguin, Edward (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.